"Live” (stained) benthic foraminiferal living depths, stable isotopes, and taxonomy offshore South Georgia, Southern Ocean: implications for calcification depths - Dejardin, Rowan; Kender, Sev; Allen, Claire S.; Leng, Melanie J.; Swann, George E.A.; Peck, Victoria L. (Geological Society, 2018)
It is widely held that benthic foraminifera exhibit species-specific calcification depth preferences, with their tests recording sediment pore water chemistry at that depth (i.e. stable isotope and trace metal compositions). This assumed depth habitat-specific pore water chemistry relationship has been used to reconstruct various palaeoenvironmental parameters, such as bottom water oxygenation. However, many deep-water foraminiferal studies show wide intra-species variation in sediment living depth but relatively narrow intra-species variation in stable isotope composition. To investigate this depth habitat- stable isotope relationship on the shelf we analysed depth distribution and stable isotopes of “living” (Rose Bengal stained) benthic foraminifera from two box cores collected on the South Georgia shelf (ranging from 250–300 m water depth). We provide a comprehensive taxonomic analysis of the benthic fauna, comprising 79 taxonomic groupings. The fauna shows close affinities with shelf assemblages from around Antarctica. We find “live” specimens of a number calcareous species from a range of depths in the sediment column. Stable isotope ratios (δ13C and δ18O) were measured on stained specimens of three species, Astrononion echolsi, Cassidulinoides porrectus and Buccella sp. 1, at 1 cm depth intervals within the down-core sediment sequences. In agreement with studies in deep water settings, we find no significant intraspecies variability in either δ13C foram or δ18O foram with sediment living depth on the South Georgia shelf. Our findings add to the growing evidence that infaunal benthic foraminiferal species calcify at a fixed depth. Given the wide range of depths that we find “living” ‘infaunal’ species, we speculate that they may actually calcify predominantly at the sediment-seawater interface, where carbonate ion concentration and organic carbon availability is at a maximum.